Sobre las propiedades temporales y aspectuales: el pretérito en la construcción «estar» + gerundio - Nowikow, Wiaczesław (Wydawnictwo Naukowe UAM, 2003)
The paper presents the different questions related to the grammatical status of the construction “ester" + gerund (està cantando) in the modern Spanish language. The author concentrates with special attention on the use of Preterite in the a.m. construction (estuvo cantando) and on the distinctionbetween temporal and aspectual properties in the description of this paraphrase. In particular, the most important property of estuvo cantando is the expression of the actions ‘in course’, but, at the same time, ‘limited in time’.